DETERMINANTS OF CHOICE AND USE OF EDUCATIONAL TECHNOLOGY FOR TEACHER PREPARATION IN KENYAN UNIVERSITIES - Marcella Mwaka; Okumu Bigambo (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿Technology is continually evolving and improving, as students increasingly become very tech savvy. In response, teachers are beginning to integrate many different technologies into their daily lessons. They are finding that students are more motivated by combining technology and learning and this ultimately helps maximize a teacher’s overall effectiveness. This approach does not come without drawbacks. Technology is not cheap or easy to maintain, but many would argue that the benefits of such an approach are well worth the money and the effort.This paper presents findings from a study whose purpose was to examine the choice and use of educational technology for teacher preparation in Kenyan universities. The study was guided by the drive theory of motivation and adopted a descriptive survey research design. Data was collected from four universities selected from ten Kenyan universities engaged in teacher preparation programs. Two hundred and thirteen fourth year students, four Heads of Department, and forty lecturers from the selected universities participated in the study. Data on choice and use of educational technology in teacher preparation was collected using questionnaire, interview, and observation schedules and analyzed using both descriptive and inferential statistics.This study established that lecturers were both inward- and outward- looking in their choice and use of educational technology with no difference between the two types of universities, lecturers are yet to be effective in the choice and use of new and emerging technologies and that lecturers encountered a variety of challenges in their choice and use of educational technology in teacher preparation. Based on these findings, the study recommends that teacher education institutions need to have a far-reaching vision for the effective use of technology in education to help their graduates to be better educated and better prepared for the evolving demands of the new economy and changing society.